Host plants and associated trophobionts of the weaver ant Oecophylla longinoda Latreille (Hymenoptera Formicidae) in Benin - (:unkn) unknown (My University, 2022)
The African weaver ant Oecophylla longinoda builds woven leaf nests inside tree canopies and is a major conservation biocontrol agent in sub-Saharan Africa. Weaver ant colonies provide well-protected and resource-rich environments for many associated trophobionts, thereby boosting their establishment on host plants. There is very little published literature on O. longinoda, their hosts plants and their associated trophobionts in West Africa. These tri-trophic interactions were studied over a period of four consecutive years (2010–2013) from south to north Benin. Our fieldwork revealed that all O. longinoda colonies were consistently associated with trophobionts. Oecophylla longinoda nests were recorded on 82 plant species belonging to 30 families, with 35 associated trophobiont species representing 11 families. Among cultivated plants, Mangifera indica was the most common species hosting O. longinoda, while Sarcocephalus latifolius the most frequent native one. Among trophobionts, Parasaissetia nigra, Udinia catori, Udinia farquharsoni (Coccidae) and Stictococcus sjostedti (Stictococcidae) were the most common hemipterans associated with O. longinoda. We identified a wide range of host plants that could be preserved (or planted) to promote the establishment of weaver ants to control different insect pests in fruit plantations in sub-Saharan Africa. When planted around fruit plantations with their nests and tended hemipterans, these host plants could facilitate biocontrol of mango fruit flies (Tephritidae) and cashew bugs (Coreidae, Miridae), by O. longinoda in the fruit plantations.
Keywords: African Research